DOI: 10.20868/upm.thesis.56799
|View full text |Cite
|
Sign up to set email alerts
|

Una visión organizativa de los programas de promoción de la salud en las empresas europeas: la influencia de la actividad física y razones de aplicación a la prostatitis crónica

Abstract: xix grasa en los sujetos de una empresa española cuyas ocupaciones se basaban en tareas sedentarias. Asimismo, el programa también afectó a la salud física y mental percibida de los sujetos, aunque los efectos fueron pequeños. De igual modo, todavía hay pocos estudios que determinen el efecto de la actividad física en CP / CPPS y no es posible proporcionar evidencia científica suficiente para evaluar su efectividad y el diseño posterior de las intervenciones en el lugar de trabajo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 215 publications
0
3
0
Order By: Relevance
“…Other recent studies found no conclusive results either, showing effects associated with increased health status (Bize & Plotnikoff, 2009). In Spain, previous research manifested the need to carry out new investigations maximizing methodological quality (Jiménez, 2019;Zafra et al, 2017). A recent study found that there could be greater job dissatisfaction among graduate employees with lower wages (Das et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other recent studies found no conclusive results either, showing effects associated with increased health status (Bize & Plotnikoff, 2009). In Spain, previous research manifested the need to carry out new investigations maximizing methodological quality (Jiménez, 2019;Zafra et al, 2017). A recent study found that there could be greater job dissatisfaction among graduate employees with lower wages (Das et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…It is therefore important to aim at Jobs where there is a greater incidence of mental illness (Bauer et al, 2014;González et al, 2017). Since the beginning of the 60s, the development of health policies, with the aim of emphasizing preventive measures, has gained greater importance in the plans of different business organizations (Durán, 2010;Jiménez, 2019;Lemon et al, 2009). Similarly, many companies try to highlight the wellbeing of their employees in order to favor the best conditions for maximum performance and productivity according to their nancial objectives (Bertera, 1990;Cox et al, 1981;Haskell, 1989;Shephard, 1995;van der Voordt, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation